2021
DOI: 10.3390/ijms22115595
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Respiratory Factor-1, a Novel SMAD4 Binding Protein, Represses TGF-β/SMAD4 Signaling by Functioning as a Transcriptional Cofactor

Abstract: SMAD4, a key regulator of transforming growth factor-β (TGF-β) signaling, plays a major role in cell growth, migration, and apoptosis. In particular, TGF-β/SMAD induces growth arrest, and SMAD4 induces the expression of target genes such as p21WAF1 and p15INK4b through its interaction with several cofactors. Thus, inactivating mutations or the homozygous deletion of SMAD4 could be related to tumorigenesis or malignancy progression. However, in some cancer types, SMAD4 is neither mutated nor deleted. In the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…In PC3 prostate cancer cells, we observed that the enhanced mitochondrial biogenesis by NRF1 may lead to suppression of TGF-β signaling and subsequent EMT. This finding is consistent with a recent study showing that NRF1 served as a Smad4 binding protein to inhibit TGF-β signaling in tumorigenesis (20). On the other hand, the present study has several limitations.…”
Section: Discussionsupporting
confidence: 92%
“…In PC3 prostate cancer cells, we observed that the enhanced mitochondrial biogenesis by NRF1 may lead to suppression of TGF-β signaling and subsequent EMT. This finding is consistent with a recent study showing that NRF1 served as a Smad4 binding protein to inhibit TGF-β signaling in tumorigenesis (20). On the other hand, the present study has several limitations.…”
Section: Discussionsupporting
confidence: 92%
“…We conducted a eukaryotic-expressed human protein array (ProtoArray) with purified SMAD4, identifying the mitochondrial protein, MMAB, as a novel SMAD4 binding protein ( Rajasekaran et al, 2021 ). The SMAD4 and MMAB interaction was assessed using a BiFC assay, allowing the detection of the subcellular localization of the SMAD4-MMAB complex in live cells.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous protein array study identified MMAB as a novel SMAD4 binding partner ( Rajasekaran et al, 2021 ). Although the inhibitory effects of SMAD4 on cancer progression are well-known, the regulatory mechanisms independent of its transcriptional function are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The transforming growth factor (TGF)-β pathway, with its role as a regulatory cytokine, has been involved in the pathophysiology of MDD ( Lee and Kim, 2010 ). It is known that NRF-1, as an important regulator of GTF2F2, can interfere with the TGF-β/SMAD pathway with a novel negative regulation of SMAD4 ( Rajasekaran et al, 2021 ). From our results, GTF2F2 may affect the TGF-β pathway through NRF-1, and therefore, associate with MDD progression.…”
Section: Discussionmentioning
confidence: 99%